Selected Abstracts of the 6th International Congress of UENPS; Valencia (Spain); November 23rd-25th 2016; Session "Heart and development" - - (Hygeia Press di Corridori Marinella, 2016)
Selected Abstracts of the 6th International Congress of UENPS; Valencia (Spain); November 23rd-25th 2016; Session "Heart and development" ABS 1. MANAGEMENT OF PATENT DUCTUS ARTERIOSUS IN TWO TERTIARY NEONATAL UNITS • D. Panjwani, J. Kapur, V Rasiah, K. Gurgusamy ABS 2. NT-PROBNP LEVELS AT 48-96 HOURS OF LIFE CAN PREDICT THE NEED FOR TREATMENT OF A HEMODYNAMICALLY SIGNIFICANT PATENT DUCTUS ARTERIOSUS IN VERY LOW-BIRTH-WEIGHT INFANTS • S. Rodriguez-Blanco, I. Oulego-Erroz, S. Gautreaux-Minaya, M. Couce-Pico ABS 3. THE ASSOCIATION BETWEEN NIRS AND DOPPLER ULTRASONOGRAPHY IN PRETERM INFANTS • D. Arman, S. Sancak, T. Gursoy, S. Topcuoglu, G. Karatekin, F. Ovali ABS 4. CARDIOVASCULAR RISK: SCHEDULED OR NOT? • B. Riaño, M. Ruiz, MY. Ruiz, P. Ventura, MP. Samper ABS 5. POSTNATAL OUTCOME OF FETAL TACHYARRHYTHMIAS: 7-YEAR TERTIARY NEONATAL INTENSIVE CARE UNIT EXPERIENCE • P. Mikrou, M. Borooah, S.V. Rasiah ABS 6. POSTNATAL SUPRAVENTRICULAR TACHYCARDIA: 7-YEAR EXPERIENCE IN A TERTIARY NEONATAL INTENSIVE UNIT • P. Mikrou, M. Borooah, S.V. Rasiah ABS 7. LOWER HYDRATION IN NEONATES WITH CONGENITAL HEART DEFECT DOES NOT CAUSE THE INCREASE IN PLASMA COPEPTIN CONCENTRATION - PRELIMINARY DATA • A. Suchojad, A. Tarko, S. Simonova, J. Kordyś, I. Maruniak-Chude ABS 8. CONGENITAL HEART DISEASE IN NEWBORNS: SIGNS AND SYMPTOMS • B. Miljkovic, M. Jonovic, N. Stojanovic, G. Jovanovic ABS 9. DIAGNOSIS OF CONGENITAL HEART DEFECTS IN A TERTIARY HOSPITAL (2010-2016) • G. Sierra, I. Naberan, N. Lecumberri, S. Torrus, N. Jordá, I. Gil ABS 10. CORRELATION OF FRACTIONAL SHORTENING, EJECTION FRACTION AND BLOOD PRESSURE IN PREMATURE INFANTS • N. Lee, S. Yun, S. Chae, I. Lim ABS 11. A WINDOW OF OPPORTUNITY FOR PDA TREATMENT • P. Priego, I. Tofe, MD. Cañete, M. Parraga ABS 12. PARACETAMOL AS A POSSIBLE TREATMENT OF CHOICE FOR PATENT DUCTUS ARTERIOSUS • S. Rodriguez-Blanco, R. Galvez-Criado, I. Oulego-Erroz, A. Perez-Muñuzuri ABS 13. PARACETAMOL FOR DUCTAL CLOSURE, A SINGLE CENTER EXPERIENCE • M. Ramon, R. Porta, E. Capdevila, V. Acosta, J. Girona, J. Fernández ABS 14. EFFICACY OF PRENATAL ULTRASONOGRAPHY IN DIAGNOSING CARDIOVASCULAR ANOMALIES • A. Beke, F.R. Eros, I. Szabo, J.Jr. Rigo ABS 15. OUTCOME OF NEONATES WITH CRITICAL CONGENITAL HEART DISEASE HOSPITALIZED IN AN INTENSIVE CARE UNIT OF A TERTIARY HOSPITAL • A. Giannakopoulou, F. Anatolitou, H. Fanaraki, P. Loukeri, M. Koumenidou, N. Lipsou, E. Karanasios, A. Kourtesis, H. Bouza ABS 16. SEASONAL DISTRIBUTION OF CONGENITAL HEART DISEASE • A. Giannakopoulou, F. Anatolitou, H. Fanaraki, P. Loukeri, K. Chatzikonstantinou, M. Dasopoulou, E. Karanasios, H. Bouza ABS 17. SOCIOECONOMIC FACTORS ASSOCIATED WITH CONGENITAL HEART DISEASE IN NEONATES • F. Anatolitou, A. Giannakopoulou, H. Fanaraki, P. Loukeri, F. Stripeli, C. Petropoulou, E. Karanasios, H. Bouza ABS 18. ASYMPTOMATIC PERICARDIAL EFFUSION IN A PRETERM INFANT WITH UMBILICAL VENOUS CATHETER • B. García, L. Domingo, D. Pérez, A. Vidal, MJ. Rivero, S. De Las Heras, M. Cuadrado ABS 19. PERSISTENT PULMONARY HYPERTENSION OF THE NEWBORN: EXPERIENCE OF A TERTIARY CARE UNIT IN PORTUGAL • S. Lopes, S. Aires, I. Ferreira, C. Carvalho, D. Oliveira, A. Almeida, S. Álvares, A. Guedes, S. Proença ABS 20. OVERVIEW OF A CASE OF HYPERTROPHIC CARDIOMYOPATHY IN A NOONAN SYNDROME PATIENT IN OUR HOSPITAL • C. Tripodi, J. Comuñas, E. Berbel, F. Camba, A. Gregoraci, S. Hernandez ABS 21. BRIEF RESOLVED UNEXPLAINED EVENTS (BRUE) DURING THE FIRST YEAR OF LIFE IN EX-PRETERM INFANTS DISCHARGED HOME WITH AND WITHOUT CAFFEINE • V. Mugarab-Samedi, J. Rabi, N. Hassanova, F. Samedi, O. Khassan, M. Nofil, A. Nettel-Aguirre, C. Fajardo ABS 22. EFFECTS OF A PATENT DUCTUS ARTERIOSUS ON INTESTINAL MUCUS BARRIER IN PRETERM NEWBORNS • N.F. Panakhova, S.Sh. Hasanov, A.I. Adilova, F.O. Seyidbeyova ABS 23. NEONATAL CONGESTIVE HEART FAILURE DUE TO AN INTRACRANIAL PIAL ARTERIOVENOUS FISTULA • R. Valsassina, S.N. Prado, M. Nunes, P. Vilela ABS 24. TRANSIENT LEFT VENTRICULAR DYSFUNCTION OF THE NEWBORN: ABOUT TWO CASES • M. Charfi, A. Bouraoui, A. Hamdi, A. Ben Thabet, R. Regaieg, A. Gargouri